(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the rate of medication adherence among patients with type 2 diabetes mellitus in Vietnam and to identify associated factors. Methods: A systematic search was conducted from January 2023 to March 2025, including 26 Vietnamese-language studies comprising from the three main regions of Vietnam. Results: The pooled medication adherence rate among type 2 diabetes mellitus patients was 0.75 (95% CI: 0.71-0.79). Regional adherence rates were 0.77 in the North, 0.74 in the Central region, and 0.74 in the South. Male patients exhibited a lower adherence rate (0.69) compared to females (0.71). Patients aged ≤ 60 years had an adherence rate of 0.74, slightly lower than those > 60 years (0.75). Patients with a diabetes duration of 5 years or more demonstrated higher adherence (0.78) than those with a duration of 5 years or less (0.70). Additionally, patients with education above high school level had a higher adherence rate (0.76) compared to those with lower educational attainment (0.72). Conclusion: Medication adherence among type 2 diabetes mellitus patients in Vietnam is relatively high. Geographic region, age, sex, disease duration, and educational level are significant factors associated with medication adherence.